TESTING THE RELIGIOSITY LEVEL AS A MODERATING VARIABLE TOWARDS THE PRODUCTIVITY LEVEL AND THE ECONOMIC INDEPENDENCE OF WOMEN SONGKET WEAVERS - Baiq Elbadriati; Sabrang Gilang Gemilang; Vici Handalucia (ULUL ALBAB Jurnal Studi Islam, 2022)
The article examines the effect of productivity level towards the economic independence of women songket weavers and their religiosity level as a moderating variable. The research was conducted in Sukarara Village, Central Lombok, NTB Province, Indonesia, by involving 1,791 women songket weavers in the area. Cluster random sampling technique was applied, and the data were analyzed quantitatively using several tests, namely instrument research, classic assumption, Moderated Regression Analysis (MRA) or interaction and statistic tests. The data processing reveals that the level of productivity significantly influences the economic independence variable. However, the religiosity level does not moderate the relation of the productivity level and economic independence of women songket weavers when making personal and mutual decisions. The significance value is 0.998 alpha 0.05, which indicates the existence of a moderation homologizer or potential moderation. Religiosity in this research is homogenous and influences no variable. It means that most of the women songket weavers have the similar level of religiosity; thus, it cannot affect their productivity level and economic independence.